Experimental Investigation of the Bonding Behavior of High-Volume Fly Ash Self-Compacting Concrete Reinforced with Steel and GFRP Bars - Waryosh, Waleed Awad; Rasol, Bilal (International Journal of Sustainable Construction Engineering and Technology, 2023)
This paper investigated the bond strength between reinforcement steel and GFRP bars embedded in high-volume fly ash concrete and conventional concrete mixtures. This research evaluated two mixes: conventional concrete, and 50% replacement cement with Class F fly ash. According to RILEM recommendations, eight hinged beams were employed to evaluate the bond strength of the concrete mixes. This investigation showed good bonding for concrete mixes containing 50% fly ash compared to conventional concrete. GFRP bars also showed good bonding, better than steel bars in the case of small diameters (10 mm), but lower bonding in the case of larger diameters (16 mm).